Analisis Kemampuan Pemecahan Masalah Matematika Dalam Menyelesaikan Soal Cerita Berdasarkan Prosedur Polya - Sabrina Ratih Kusumaningrum; Muhammad Nailul Furqon; Wafna Jannata Ulya; Fitriyah Amaliyah (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
Problem solving skills are important for students to overcome various problems related to learning and community life. This involves students actively exploring, observing, trying, and investigating using the knowledge and abilities they have. Problem solving is the main focus of developing students' higher order thinking skills in mathematics. This research was conducted by means of observation, interviews, and post-test methods on the 4th grade students of SD Negeri 7 Gondosari. In the results of the discussion, there are 10 data from 31 students which can describe a good level of problem solving. Some students experienced difficulties in implementing the problem and re-examining the results of the solution. Therefore, it is important for students to continue to hone their problem solving abilities using the Polya procedure and to re-check the correctness of the solutions that have been done.